2008
DOI: 10.1370/afm.760
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care After Psychiatric Crisis: A Qualitative Analysis

Abstract: PURPOSE Patients with serious psychiatric problems experience diffi culty accessing primary care. The goals of this study were to assess whether care managers improved access and to understand patients' experiences with health care after a psychiatric crisis.METHODS A total of 175 consecutive patients seeking care in a psychiatric emergency department were randomly assigned to an intervention group with care managers or a control group. Brief, semistructured interviews about health care encounters were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 20 publications
(18 reference statements)
3
29
0
5
Order By: Relevance
“…The findings concur with those of Griswold et al (2008) regarding the importance to many service users of the clinician's communication skills, particularly in regards to listening. Some of the attributes consumers consider to be important to quality MHTS provision include ease of access, helpfulness, providing choices and options, and follow-up care.…”
Section: Discussionsupporting
confidence: 86%
“…The findings concur with those of Griswold et al (2008) regarding the importance to many service users of the clinician's communication skills, particularly in regards to listening. Some of the attributes consumers consider to be important to quality MHTS provision include ease of access, helpfulness, providing choices and options, and follow-up care.…”
Section: Discussionsupporting
confidence: 86%
“…Of the RCTs, three reported some clinical benefit including improved mental and physical function [42] improved physical function [23] and reduced relapse rate [22]. RCTs by Lester and Warner [26,43] of patient-held records found no clinical or service use benefits, while a cohort study by McDonough [44] reported no clinical or service use benefit from a GP-Community Health Team shared care register.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the use of atypical antipsychotics has been implicated as an important contribution to these risks (Reist et al 2007). Finally, the excess in morbidity and mortality is also due to difficulties in accessing medical care, and to the lack of communication between systems managing mental, behavioral and physical health (Emergency Response 2005;Griswold et al 2008). This issue is all the more critical given the poor health behaviours and risks associated with antipsychotic medications that characterize many of these patients.…”
Section: Introductionmentioning
confidence: 99%